Dipterofauna with enphasis in Muscidae associated to cattle manure in a tropical organic dairy system from Brazil - de Freitas, Aline Quintanilha; Florião, Mônica Mateus; Lourenço, Elizabete Captivo; Borja, Gonzalo Efraín Moya; Couri, Marcia Souto; Famadas, Katia Maria (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Freitas A.Q., Florião M.M., Lourenço E.C., Moya-Borja G.E., Couri M.S. & Famadas K.M. [Dipterofauna with enphasis in Muscidae associated to cattle manure in a tropical organic dairy system from Brazil.] Dipterofauna com ênfase em Muscidae associada às massas fecais de bovinos em sistema orgânico de produção de leite, na região tropical, Brasil. Revista Brasileira de Medicina Veterinária, 38(supl. 3):218 - 228, 2016.. Programa de Pós-Graduação em Ciências Veterinárias, Instituto de Veterinária, Universidade Federal Rural do Rio de Janeiro. Universidade Federal Rural do Rio de Janeiro. BR 465 km 7. Campus Seropédica, Rio de Janeiro, RJ 23.897-970, Brasil. E-mail: alineqf@hotmail.com. Dipterans are important members of the decomposition fauna of cattle dung and they influence the incidence of parasitic diseases in the herd. Thus, the present study aimed to make an inventory of the members of the dipterofauna associated with manure in an organic system of dairy cattle in Seropédica, State of Rio de Janeiro. Four litres of manure were collected dairy during one month in each season and immediately taken to the laboratory where we extracted the pupas of the dipterans by flotation method, and then we individualized each pupa in an Eppendorf for the emergence of the adults. After that, we identified the dipterans and tabulated the results. The Diptera families reported belonged to the families Muscidae, Sepsidae, Sarcophagidae, Stradiomyidae and Tachinidae. About the muscids, we collected the following species: Gymnodia normata, Gymnodia quadristigma, Musca domestica and Biopyrellia bipuncta.